IgG and complement receptors on purified mouse eosinophils and neutrophils. - López, A F (1981)
Mouse eosinophil and neutrophil receptors for IgG and complement have been examined by means of rosette formation, phagocytosis and 51Cr release assays, using mouse monoclonal antibodies and complement-coated sheep erythrocytes. Mouse eosinophils and neutrophils form a high number of rosettes in the presence of mouse complement but eosinophils show a higher requirement for complement molecules. Both types of granulocyte phagocytose complement-coated sheep erythrocytes very actively, although low levels of 51Cr release are obtained. Eosinophils and neutrophils show higher activity in the presence of IgG2b than in the presence of IgG1, and while both cell types are similarly active when the former antibody is used, neutrophils are the more active when IgG1 is used. However, it remains uncertain whether this is a result of the higher binding obtained with the IgG2b monoclonal antibody. Both cell types behave similarly at high antibody concentrations but neutrophils are the more active at high antibody dilutions. The 51Cr release assay is shown to be superior to the rosette assay at it allows comparisons between eosinophils and neutrophils at high antibody concentrations. A time course study indicates that highest values of phagocytosis of opsonized red cells are obtained after 5 minutes rather than the half to one hour incubation periods normally used.